2018
DOI: 10.1002/aoc.4235
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole/Fe3O4/CNT as a recyclable and highly efficient catalyst for one‐pot three‐component synthesis of pyran derivatives

Abstract: Polypyrrole (PPY)/Fe 3 O 4 /CNT has been synthesized and characterized by FT-IR, TEM and SEM techniques and its catalytic activity has been evaluated in the synthesis of several series of pyran derivatives. Tetrahydrobenzo[b]pyranes, 4Hpyran-3-carboxylates, 4H,5H-pyrano[3,2-c]chromenes and dihydropyrano[2,3-c] pyrazoles have been successfully prepared from one-pot three-component condensation of aldehyde, malononitrile and active methylene-containing compounds (dimedone /ethyl acetoacetate/4-hydroxycoumarin/3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] The primary advantages of ternary nanocomposites are the synergistic effect between the three components, resulting in excellent electronic, optical, sensing, catalytic, magnetic properties, environmental and thermal stability. [17][18][19][20][21][22][23][24][25][26][27][28] Polymer-metalcarbon nanomaterials based on conjugated polymers can be used in magnetic information recording systems, for medical purposes, as electromagnetic radiation absorbing materials, to create sensors and nanoprobes, rechargeable batteries, and other electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] The primary advantages of ternary nanocomposites are the synergistic effect between the three components, resulting in excellent electronic, optical, sensing, catalytic, magnetic properties, environmental and thermal stability. [17][18][19][20][21][22][23][24][25][26][27][28] Polymer-metalcarbon nanomaterials based on conjugated polymers can be used in magnetic information recording systems, for medical purposes, as electromagnetic radiation absorbing materials, to create sensors and nanoprobes, rechargeable batteries, and other electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…To reveal the advantages of this catalyst, its catalytic activity in the model reaction involving benzaldehyde, malononitrile and 4‐hydroxycoumarin was compared with those of previously reported systems (Table ). As evident from Table , the catalytic activity of Ag 3 PMo 12 O 40 was compared with other catalysts such as [DMAP‐PEG 1000 ‐DI L][BF 4 ], nano‐ZnO, crown ether complex cation ionic liquids (CECILs), ammonium acetate, titanium dioxide nanowires, nanomagnetic double‐charged diazoniabicyclo[2.2.2]octane dichloride silica hybrid (Fe 3 O 4 @SiO 2 /DABCO), surfactant‐modified bentonite (CTMAB‐bentonite), hexamethylenetetramine, SiO 2 /H 3 PW 12 O 40 nanohybrid, RuBr 2 (PPh 3 ) 4 , sodium malonate, NaCl, (NH 4 ) 42 [MoVI 72 MoV 60 O 372 (CH 3 COO) 30 (H 2 O) 72 ], a Keplerate‐type giant‐ball nanoporous isopolyoxomolybdate, silica‐supported molybdic acid, KNaC 4 H 4 O 6 ⋅4H 2 O (potassium sodium tartrate) and polypyrrole/Fe 3 O 4 /CNT that were previously used as catalysts in the same reaction. The results showed that compared to the other catalysts, our designed catalyst can catalyse the reaction in an appropriate manner.…”
Section: Resultsmentioning
confidence: 99%
“…The development of a simple and green method for the synthesis of 2′‐aminospiro[indeno[1,2‐ b ]quinoxaline‐11, 4′‐[4'H]pyran]‐3′‐carbonitrile using an inexpensive and environmentally benign catalyst is therefore in demand. In continuation of our interest in the development of green catalytic methods for the preparation of biologically active heterocycles, we report here for the first time the application of magnetically separable copolymer (polyaniline‐polypyrrole)@GO‐Fe 3 O 4 in the four‐ and three‐component synthesis of 2′‐aminospiro[indeno[1,2‐ b ]quinoxaline‐11, 4′‐[4'H]pyran]‐3′‐carbonitrile and 2′‐aminospiro[indeno‐2,4′‐[4'H]pyran]‐3′‐carbonitrile derivatives.…”
Section: Introductionmentioning
confidence: 99%